Konsep Manusia Sebagai Imago Dei Dan Implikasinya Terhadap Konseling Alkitabiah - Laurina, Connie (Kaluteros Jurnal Teologi Dan Pendidikan Agama Kristen, 2024)
Human life is inevitably intertwined with problems and difficulties. At times, individuals struggle to overcome the challenges they face, which can affect their thinking patterns and behaviors, leading to anxiety and depression. Counseling emerges as a vital service in human life to address these issues. There exist various methods and practices in counseling aimed at assisting individuals in resolving their problems. However, there lies a distinction between Secular Counseling and Biblical Counseling. This article emphasizes Biblical Counseling oriented towards and sourced from God's declarations. The aim of this research is to delve into matters related to: the significance of Anthropology in counseling, the concept of the Image of God within humanity, the purpose of human creation in Imago Dei, the connection between the fall of humanity and Imago Dei, and the implications of the Imago Dei concept in Biblical Counseling.